2018
DOI: 10.1002/chem.201803839
|View full text |Cite
|
Sign up to set email alerts
|

Fast and pH‐Independent Elimination of trans‐Cyclooctene by Using Aminoethyl‐Functionalized Tetrazines

Abstract: The inverse-electron-demand Diels-Alder/pyridazine elimination tandem reaction, in which the allylic substituent on trans-cyclooctene is eliminated following reaction with tetrazines, is gaining interest as a versatile bioorthogonal process. One potential shortcoming of such currently used reactions is their propensity to proceed faster and more efficiently at lower pH, a feature caused by the nature of the tetrazines used. Here, we present aminoethyl-substituted tetrazines as the first pH-independent reagents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(77 citation statements)
references
References 29 publications
8
69
0
Order By: Relevance
“…The authors confirmed that release occurred from the 1,4‐tautomer; however, the 2,5‐tautomer also forms, and tautomerization to the 1,4‐tautomer is required to achieve quantitative yields of elimination. It was observed that lowering the pH increased release yields; this observation prompted the synthesis of tetrazines with acid‐functionalized substituents . Tetrazines with a propanoic acid group (e.g., 2 ; Scheme ) facilitated tautomerization by general acid catalysis and released products rapidly and at high yields at physiological pH .…”
Section: Reported Dissociative Bioorthogonal Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors confirmed that release occurred from the 1,4‐tautomer; however, the 2,5‐tautomer also forms, and tautomerization to the 1,4‐tautomer is required to achieve quantitative yields of elimination. It was observed that lowering the pH increased release yields; this observation prompted the synthesis of tetrazines with acid‐functionalized substituents . Tetrazines with a propanoic acid group (e.g., 2 ; Scheme ) facilitated tautomerization by general acid catalysis and released products rapidly and at high yields at physiological pH .…”
Section: Reported Dissociative Bioorthogonal Reactionsmentioning
confidence: 99%
“…Tetrazines with a propanoic acid group (e.g., 2 ; Scheme ) facilitated tautomerization by general acid catalysis and released products rapidly and at high yields at physiological pH . Tetrazines with ethylammonium substituents (e.g., 4 ; Scheme ) also benefit from general acid catalysis and efficiently facilitate elimination over a broad pH range (3.5–7.5) . Computational studies revealed that, in addition to benefitting from general acid catalysis of the tautomerization step, such substituents also favor the regioselective initial formation of the releasing 1,4‐tautomer …”
Section: Reported Dissociative Bioorthogonal Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“… A) Reaction mechanism of “click and release” strategy with the TCO‐Tetrazine pair. Substituent effects of the fundamental IEDDA and tautomerization steps are indicated, together with the leaving groups that have been described so far . B) Molecular structure of the TCO‐Tetrazine pair used for targeted delivery of MMAE in tumor‐bearing mice: the drug is connected to a monoclonal antibody in diabody format through a TCO linker (ADC 65 ) and released by reaction with tetrazine 66 , 48 h post ADC injection.…”
Section: When and Where: Linker Cleavage Promoted By External Stimulimentioning
confidence: 99%
“…In 2018, Weissleder reported a reaction between tetrazines and TCO derivatives that revealed a strong pH dependency, with the authors synthesising tetrazines bearing acid moieties that promoted efficient release of TCO‐linked cargo . Van Kasteren reported a library of pH‐independent tetrazines that contained both an EWG group and an aminomethyl functionality, which acts as an intramolecular catalyst for the tautomerisation, thus accelerating the elimination step in different physiological buffers . Some tetrazines have been shown to have good stability in biological media such as FBS and, thus, be suitable for in vivo applications.…”
Section: Tetrazines As Activators For Prodrugsmentioning
confidence: 99%